Changes and their effects on working and daily life time use allocation between work-from-home and office work days during the telework period: insights from the survey in Japan - Eri Aoki; Eri Aoki; Ai Hiramatsu; Keisuke Hanaki (Frontiers in Sociology)
IntroductionThe rapid adoption of telework, accelerated by advancements in ICT and the COVID-19 pandemic, offers potential benefits for wellbeing and environmental impact. However, telework’s effects on work productivity, work-life balance, and social connectedness remain complex, particularly within hybrid models combining work-from-home (WFH) and in office days.MethodsThis study assessed telework’s impact by comparing WFH and office days. A survey of 1,500 full-time workers in Japan’s Tokyo Metropolitan Region focused on daily time allocation, and telework preferences during telework periods. Principal component and cluster analyses were used to identify groups with distinct work and lifestyle patterns.ResultsSix telework-related groups emerged, reflecting diverse experiences in productivity and daily life. Groups such as the “Overall Increase” and “Housework and Rest Increase” reported gains in leisure and family time, positively impacting wellbeing. In contrast, the “Unsuitable for WFH” group faced increased office-day workloads and reduced WFH productivity, indicating that telework’s effectiveness depends on job and individual characteristics.ConclusionThe findings highlight telework’s potential to enhance wellbeing and sustainability but also underscore the need for tailored policies that address diverse job requirements and personal characteristics. This study contributes to sustainable telework strategies by offering insights into effective support systems that balance flexibility, productivity, and environmental sustainability, aiming both for an enhanced personal life and societal benefits.